1985
DOI: 10.1071/ph850273
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Charges and Electron Density Partitioning

Abstract: Aust. J. Phys., 1985, 38, 273-87 Atomic charges are derived from two dissimilar methods of partitioning the electron density of diatomic molecules. The results given by both methods are similar, with the exception of those for molecules containing lithium; factors responsible for this discrepancy are explored. The charges derived are correlated closely with electronegativity differences and with dipole moments. They follow chemically sensible trends and have reasonable magnitudes. The partitioning methods u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
1
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 23 publications
2
48
1
1
Order By: Relevance
“…Maslen & Spackman (1985) have shown that other quite disparate methods of partitioning the deformation electron density yield essentially the same results. The Hirshfeld partitioning is simple to apply and yields a smooth continuous Apa(r).…”
Section: Apa(r)=[pat°m(r)/ppr°(r)]ap(r)supporting
confidence: 56%
See 4 more Smart Citations
“…Maslen & Spackman (1985) have shown that other quite disparate methods of partitioning the deformation electron density yield essentially the same results. The Hirshfeld partitioning is simple to apply and yields a smooth continuous Apa(r).…”
Section: Apa(r)=[pat°m(r)/ppr°(r)]ap(r)supporting
confidence: 56%
“…It was found that, for all the diatomics studied, the atomic charges determined by numerical integration in this range were insignificantly different from those obtained by Maslen & Spackman (1985), who performed a numerical integration over r from zero to infinity by Gaussian quadrature. Values of the integrand in (6) for each of the diatomics were effectively zero at distances greater than 10a.u.…”
Section: Apa(r)=[pat°m(r)/ppr°(r)]ap(r)mentioning
confidence: 95%
See 3 more Smart Citations